Urine Analyzer : A Development Project of an Urine Analyzer for IDEXX Laboratories - Norstedt Jannerlid, Emmy; Tenglund, Linn (2015)
As a Bachelor thesis for two Swedish students from Luleå University of technology, a project was imple-mented at IDEXX Laboratories, Westbrook, Maine, USA in autumn 2014. IDEXX Laboratories is a diag-nostic product development company that develops products for veterinarians and technicians.The assignment was to develop one of IDEXX Laboratories new products for urine analysis that is current-ly, only available as a prototype. The goal has been to identify user needs to be able to design an intuitiveproduct with small margins for error.From the identified uses needs, a mission statement was made.“A reliable product that is easy to use and deliver fast results.”From the identified user needs, research questions for the project were compiled. Those have been:How can the design be made more intuitive for users?How can the functions be integrated into one design the best possible way?How can the design be integrated with IDEXX design guidelines?How can we prevent accidental cuvette spill from the cuvette holder by the users?How can we change the design of the cuvette holder without removing the only one way fit in the instru-ment?Through creative methods such as morphological analysis, brainstorming and Osborn’s checklist, solu-tions for all the six interaction points were developed. These were illustrated by sketches, drawings andCAD models which were then used in the evaluations of the ideas and the concepts. The concepts werefurther developed and down selected to eventually become two final concepts.The first one, Vänorts, is a concept for the instrument door, with buttons, waste drawer and other intuitivesolutions, to make the workflow for the veterinarians easier.The second final concept, Dalälven, is a solution for the Cuvette holder and the holder attachment. Thesolution will prevent the users from accidentally remove the Cuvette holder and spill all the Cuvettes andit still has the one way fit.The final concept including final recommendations of further development will be submitted to IDEXXLaboratories, ...